Prevalence of consumption of psychoactive substances amongst Moroccan taxi drivers - Laraqui, Omar; Laraqui, Salwa; Manar, Nadia; Ghailan, Tarik; Hammouda, Reda; Deschamps, Frédéric; Laraqui, Chakib El Houssine (La Medicina del Lavoro, 2018)
Background: The prevalence of psychoactive substances is constantly increasing in developing countries, and all professional sectors are concerned. Taxi drivers are a particular target because of the dangerousness and complexity of their work. However, few studies have investigated toxic habits in this population. Objectives: The aim of the study was to determine the prevalence of the use and misuse of addictive substances in taxi drivers and to appreciate poly-consumptions according to socio-demographic and occupational characteristics. Methods: This cross-sectional study took place in five big cities during the second quarter of 2014, and was conducted amongst 2,927 taxi drivers who went through official, obligatory control areas on a daily basis. The questionnaire covered socio-demographic and occupational characteristics, toxic habits (tobacco, alcohol, cannabis and others psychotropic substances). The misuse was assessed by specific tests: Fagerström test for tobacco smoking, Cannabis Abuse Screening Test (CAST) and DETA (Diminuer, Entourage, Trop, Alcool) test for alcohol. Results: The prevalence of consumption was 36.6% for smoking tobacco, 18.4% for cannabis, and 10.5% for alcohol. Amongst consumers, the prevalence of dependence or misuse was 36.6% for smoking tobacco, 37.2% for cannabis and 56.5% for alcohol. Fifty point three percent had no toxic habit, 35 % had one toxic habit, 11.5% had two toxic habits, 2.7% had three toxic habits and 0.6% had four toxic habits. The most frequent associations were tobacco-alcohol (6.8%) and tobacco-cannabis (4.1%). Conclusions: The elaboration of the prevention approach needs a cooperative spirit. It will be more accepted and applied if all taxi drivers, their representatives and road safety officers are involved in its preparation.